2009
DOI: 10.1097/prs.0b013e3181babb93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Axonal Load on the Functional and Aesthetic Outcomes of the Cross-Facial Nerve Graft Procedure for Facial Reanimation

Abstract: The axon count at the donor nerve has a stronger influence on the final results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 27 publications
3
72
0
1
Order By: Relevance
“…Despite the mixed evidence of the outcomes in experimental studies, the clinical presentation in this population was more benevolent than expected. Terzis, Wang, and Zhao () noted that in patients with axonal load lower than the threshold, there remained 45% of patients that achieved good to excellent functional results. Causes for acceptable outcome in this population may be due to (a) a strong desire to acquire an acceptable functional recovery combined with (b) a lower expectation to gain symmetry aesthetically, and (c) weakened contralateral facial muscles that lower the threshold to achieving symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the mixed evidence of the outcomes in experimental studies, the clinical presentation in this population was more benevolent than expected. Terzis, Wang, and Zhao () noted that in patients with axonal load lower than the threshold, there remained 45% of patients that achieved good to excellent functional results. Causes for acceptable outcome in this population may be due to (a) a strong desire to acquire an acceptable functional recovery combined with (b) a lower expectation to gain symmetry aesthetically, and (c) weakened contralateral facial muscles that lower the threshold to achieving symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other jump interpositional nerve graft hypoglossal‐facial neurorrhaphy procedures, our patients whose preoperative paralysis of 6 months or less achieved good results, showing the effectiveness of our procedure for patients with relatively short preoperative paralysis. Terzis et al reported on the effect of axonal load on the functional and aesthetic outcomes of the cross‐facial nerve graft. In this report, they concluded that the axon count at the donor nerve had a stronger influence on the final result .…”
Section: Discussionmentioning
confidence: 99%
“…Terzis et al reported on the effect of axonal load on the functional and aesthetic outcomes of the cross‐facial nerve graft. In this report, they concluded that the axon count at the donor nerve had a stronger influence on the final result . In our procedure, we only created an epineural window.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our various trials for improving CFNG procedure, our result showed suboptimal results especially in lip elevation and excursion, as clarified in many previous studies (Hembd et al, 2017;Snyder-Warwick et al, 2015;Terzis, Wang, & Zhao, 2010). (Figure 4) Therefore, additional muscle transfer is commonly performed for sufficient and symmetric lip excursion and smiling.…”
Section: Discussionmentioning
confidence: 56%